F29. Recovery of sensory modalities after peripheral nerve lesions associated with mechanoreceptor and sensory nerve fiber function. (May 2018) - Krarup, Christian; Rosén, Birgitta; Boeckstyns, Michel; Sørensen, Allan Ibsen; Lundborg, Göran; Moldovan, Mihai; Archibald, Simon
Abstract : Introduction: Sensation is essential for recovery after peripheral nerve injury. However, the relationship between sensory modalities and function of regenerated fibers and reinnervated sensory receptors is uncertain. We have investigated the relationships between touch threshold, tactile gnosis and mechanoreceptor and sensory fiber function after nerve regeneration. Methods: Twenty-one median or ulnar nerve lesions were repaired by a collagen nerve conduit or direct suture. Quantitative sensory hand function using a modified Rosen score and sensory conduction studies by near-nerve needle technique including tactile stimulation of mechanoreceptors were followed for 2 years, and results were compared to non-injured hands. Results: At both repair methods, touch thresholds at the finger tips recovered to 81 ± 3% whereas tactile gnosis only recovered to 20 ± 4% (P < 0.001) of control. The sensory action potentials (SNAPs) remained dispersed and areas recovered to 23 ± 2% whereas the amplitudes only to 7 ± 1% (P < 0.001) of control. The areas of SNAPs after tactile stimulation recovered to 61 ± 11% and the latencies remained 62 ± 7% prolonged. Touch sensation correlated with SNAP areas (P < 0.005) and was negatively related to the prolongation of tactile latencies (P < 0.01); tactile gnosis was not related to electrophysiological parameters. Conclusion: The recovered function of regenerated peripheral nerve fibers and reinnervated mechanoreceptors may differentially influence recovery of sensory modalities. Touch was affected by the number and function of regenerated fibers and mechanoreceptors. In contrast, tactile gnosis depends on the input and plasticity of the CNS, which may explain the absence of a direct relation between electrophysiological parameters and poor recovery. Dispersed maturation of sensory nerve fibers with desynchronized inputs to the CNS also contributes to the poor recovery of tactile gnosis.